Differences between employees and managers regarding emotional competences - Nikić, Gordana; Travica, Vesna; Mitrovic, Milena (Serbian Journal of Management, 2014)
The main goal of this paper is to examine differences between employees and managers in attachment styles, emotional intelligence, life satisfaction, personality traits and humour styles, as well to discuss implications of this connection to the quality of management at work. The survey includes 240 participants from Serbia. The sample includes employees and managers of both genders and of a various age. The instruments used are: Emotional Skills and Competence Questionnaire (Takšić, Moharić, Munjas, 2006), Experiences in Close Relations (Kamenov & Jelić, 2003), Personality Questionnaire (Zuckerman, 2002), Humour Styles Questionare (Martin et al, 2003) and Satisfaction With Life Scale (Diener, 1985) . The results indicate that the owners, top managers and managers in relation to employees have higher scores on all three dimensions of emotional intelligence, dominant affiliative humour style, they are more satisfied with life and show higher activity. Employees have dominant aggressive and self-defeating humour style and neuroticism in relation to owners, managers and top managers. Keywords: attachment style, emotional intelligence, personality traits, humour styles, life satisfaction, management